BLOCKCHAIN TECHNOLOGIES:: FEATURES OF REGULATION AND APPLICATION IN LEGAL PRACTICE - Gorevoy, Evgeniy; Irekovna Kokhanovskaya, Indira; Nikiporets-Takigawa, Galina; Stanislavovna Bastrykina, Tatiana; Dmitriyevich Sekerin, Vladimir (Revista Gênero e Interdisciplinaridade, 2020)
This article discusses the features and practical problems of the legal regulation of blockchain technology. The rapid spread of digital technologies in many areas of public life has raised serious questions about the formation of legal regulation of the use of these technologies for the leadership of the world's leading economies. The purpose of this research is to analyze practical problems faced by developers of digital legislation and develop recommendations for the formation of effective organizational and legal mechanisms for their solution. The authors analyze the spheres of the possible application of blockchain technology, international approaches to the regulation of digital technologies, as well as the projected legal norms of the Russian bill on the use of digital technologies in civil circulation. The article shows the huge possibilities of using blockchain technology, as well as the possible risks of its use in certain areas. The noteworthy opinions of various scholars on the prospects for the development of legal regulation of blockchain technology in various sectors of the economy, as well as in individual institutions of the political system of the Russian Federation have been investigated. At present, regulatory regulation and judicial practice on blockchain technology in the Russian Federation has not yet been developed, but positive examples of successful application of this technology in various areas of economy and politics are already available. Conclusions are drawn, prospects for the development of legal regulation of blockchain technology in general and in certain areas of its application, in particular, the banking sector, are shown. The authors name the main goals of legal regulation that should be considered by the legislator when making additions to the current civil legislation and forming digital legislation.